Christianity, tolerance, and pluralism: a theological engagement with Isaiah Berlin's social theory - Jinkins, Michael (Routledge studies in religion, 2004)
Isaiah Berlin : a critical description of his thought from a theological perspective -- Can Christians be pluralists? : value pluralism and the gift of diversity -- The application of Isaiah Berlin's understanding of social conflict to communities of faith -- Is toleration a Christian virtue? : beyond the disrespect of enlightenment forbearance -- Epilogue in an ecclesiological key.